The Correlation Between Personal Factors of International Tourists and Tourists Behavior Who Visited Luangprabang National Museum - SIFONGXAY, Sangthong; LATTANASOUVANNAPHON, Champa; SISAVANH, Orlathai; MIXAYKONE, Khanthaly; SOULIYASACK, Somkith; INDAVONG, Dalounny; SENGDALA , Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objectives of this study were to: 1) study international tourists' behavior who visited the Luangprabang National Museum; and 2) analyze the relationships between the personal factors of international tourists and tourism behavior at the Luangprabang National Museum. Data was collected through a set of questionnaires that were distributed among 385 international tourists who visited the Luangprabang National Museum. The obtained data was then analyzed by using the Statistical Package of the Social Sciences Program. According to descriptive statistics, the data analysis tools used were percentage, mean, standard deviation, inferential statistics, and chi-square for hypothesis testing. Research results revealed that the majority of international tourists were male with an average age ranging from 20-30 years old and they were single. The level of education was bachelor degrees and most of them were employees of private companies with an average monthly income between 1000-5,000 and the USA. The analysis of the behavior of international tourists at Luangprabang National Museum found that most international tourists visited the museum for the first time, they received information about the museum from the internet, they spent an hour there, their trip was for general leisure, the time of their visit was around 8:00-11:30 am, and they mainly visited the museum on Mondays. They visited it with their friends, and most international tourists were impressed by the king’s reception room. They were unsure about coming back again in the future and unsure about telling other tourists about Luangprabang National Museum. In addition, the result of hypothesis testing indicated that personal factors such as gender, age, status, education, occupation and monthly income correlated with international tourists’ behavior in terms of the amount of time to visit, the purpose of the visit, the duration of visit, the date of visiting, travel companions, telling others, the receiving of information, the time periods of the visit and repeated visits were significant at 0.05 level.